2006
DOI: 10.2151/jmsj.84.783
|View full text |Cite
|
Sign up to set email alerts
|

Convective Cloud Systems over the Tibetan Plateau and Their Impact on Meso-Scale Disturbances in the Meiyu/Baiu Frontal Zone

Abstract: The relationship between convective activity over the Tibetan Plateau (TP) and meso-scale cloud systems in the Baiu/Meiyu frontal zone, are examined for the 1998 summer monsoon season by using GEWEX Asian Monsoon Experiment (GAME) reanalysis data and Geostationary Meteorological Satellite (GMS)-IR Tbb data.Diurnal cycle of the plateau-scale heat low associated with convective clouds is dominated, forming a plateau-scale convergence line. Moisture transport from south of TP is essential for developing convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 33 publications
2
62
0
1
Order By: Relevance
“…High-resolution convection-permitting simulations also show similar eastward propagation of precipitation over the US (Trier et al, 2006). Over the "three-step" terrain in East Asia, the summer precipitation on the TP maximizes in the afternoon to early evening, and nocturnal rainfall occurs over the Sichuan Basin (SCB) areas and precipitation phase delays over the low-lying plains (Tao, 1980;Ninomiya, 2000;Asai et al, 1998;Wang et al, 2004Wang et al, , 2005Yasunari and Miwa, 2006;Bao et al, 2011;Zipser, 2009, 2011;Sun et al, 2010;Yu et al, 2007Yu et al, , 2009). Wang et al (2004Wang et al ( , 2005 used hourly infrared (IR) brightness temperatures observed by the Geostationary Meteorological Satellite (GMS) to compile a climatology of warmseason cloud/precipitation episodes over East Asia; they found that the propagating events moved eastward at phase speed of ∼ 10-25 ms −1 and compared the similarity of cloud/precipitation events to the rain streaks in CAR02.…”
Section: Introductionmentioning
confidence: 83%
“…High-resolution convection-permitting simulations also show similar eastward propagation of precipitation over the US (Trier et al, 2006). Over the "three-step" terrain in East Asia, the summer precipitation on the TP maximizes in the afternoon to early evening, and nocturnal rainfall occurs over the Sichuan Basin (SCB) areas and precipitation phase delays over the low-lying plains (Tao, 1980;Ninomiya, 2000;Asai et al, 1998;Wang et al, 2004Wang et al, , 2005Yasunari and Miwa, 2006;Bao et al, 2011;Zipser, 2009, 2011;Sun et al, 2010;Yu et al, 2007Yu et al, , 2009). Wang et al (2004Wang et al ( , 2005 used hourly infrared (IR) brightness temperatures observed by the Geostationary Meteorological Satellite (GMS) to compile a climatology of warmseason cloud/precipitation episodes over East Asia; they found that the propagating events moved eastward at phase speed of ∼ 10-25 ms −1 and compared the similarity of cloud/precipitation events to the rain streaks in CAR02.…”
Section: Introductionmentioning
confidence: 83%
“…The Tibetan Plateau represents a huge obstacle which can block basic atmospheric flows and split the prevailing westerlies into the northern and southern branches (Yeh, 1950;Staff Member, 1957). The interaction between the westerly flow and the Tibetan Plateau causes the production of shallow vortices in the lee of the Plateau (Staff Member, 1958;Wu et al, 1985;Wang and Orlanski, 1987;Wang et al, 1993;Chang et al, 2000;Yasunari and Miwa, 2006). These vortices are obviously related to the leeside trough, and their relationship with the trough will be discussed later in a separate report.…”
Section: Mean Leeside Troughmentioning
confidence: 99%
“…In the meiyu-baiu rainband, synoptic-scale and various types of mesoscale disturbances are indeed frequently observed to propagate eastward (Ninomiya and Shibagaki 2007). Some of those mesoscale disturbances originate from so-called southwest vortices on the eastern flank of the Tibetan Plateau, which develop from the interaction of the southerly flow, orography, and convection (Tao and Ding 1981;Ding and Chan 2005;Yasunari and Miwa 2006). Sometimes the vertical coupling with mid-/upper-tropospheric disturbances can lead to strong (sub-) synoptic lows (Chang et al 1998).…”
Section: Role Of Weather Disturbancesmentioning
confidence: 99%